Quality of Gluten Free Bread with the Addition of Xanthan Gum and Different Kneading Methods - Batubara, Siti Chairiyah; Muliyana, Nur Hanifah (University of Sultan Ageng Tirtayasa, 2023)
White bread generally uses wheat as the main ingredient due to its high viscosity and elasticity in the presence of gluten. However, because gluten is an allergen, not everyone can eat white bread. The aim of this study is to determine the quality of gluten-free white bread with the addition of xanthan gum and different stirring methods by testing the physical, chemical and organoleptic properties of the product. This research was conducted using experimental research methods. The design uses a fully randomized factorial design (RALF) with two factors, namely xanthan gum concentration and different mixing methods with three replicates. This study uses the statistical ANOVA test with a significance of α<0.05. The result: the higher the xanthan gum concentration in gluten-free white bread, the higher the texture value and the lower the swelling and moisture content. The result is that the longer the fermentation time when using the dough-free method with gluten-free white bread, the higher the value of swelling power and water content, as well as the textural value decreases. The results also showed that the best treatment was the addition of a xanthan gum concentration of 1.25% and the direct dough method with a texture value of 1562.9, swelling 430.269%, moisture content 35.18%, ash content 0.945%, fat content 6.675%, protein content Was 6.71%, carbohydrate content 50.45%, Hedonic test results ranged from 3-4 (rather similar) and Hedonic quality test results for crust color attributes 3.11-3.78 (brownish-yellow ), crumb color (beige-brownish), aroma (slightly acidic). ), pore uniformity 3.33–3.55 (rather uniform), texture (slightly soft), and flavor (slightly sour). The gluten-free test did not reveal any detectable gluten content in this study.